Chuck Klosterman IV : a decade of curious people and dangerous ideas. - Klosterman, Chuck, 1972- (Scribner, 2007)
This book consists of three parts: Things That Are True: profiles and trend stories: Britney Spears, Radiohead, Billy Joel, Metallica, Val Kilmer, Bono, Wilco, the White Stripes, Steve Nash, Morrissey, Robert Plant--all with new introductions and footnotes. Things That Might Be True: opinions and theories on everything from monogamy to pirates to robots to super people to guilt and (of course) advancement--all with new hypothetical questions and footnotes. Something That Isn't True At All: This is new fiction. There's an introduction, but no footnotes. Well, there's a footnote in the introduction, but none in the story.--From publisher description.